BANTUAN LUAR NEGERI JEPANG TERHADAP PENINGKATAN RESILIENSI BENCANA GEMPA BUMI DAN TSUNAMI INDONESIA PERIODE 2015-2019: Studi Kasus Implementasi Build Back Better Di Sulawesi Tengah - Farhan Fadilah, (2022)
Disaster resilience is an issue that still receives little attention in Indonesia. As a country prone to earthquakes and tsunamis, the urgency of developing disaster resilience in Indonesia should be high. In its development, apart from domestic efforts, there are also external factors that contributes. This external factor appears in the form of foreign aid, specifically what is discussed in this research is the foreign aid provided by Japan to Indonesia where in its grant Japan implements the Build Back Better concept. In this study, foreign aid will be used as a theory on how the Japanese Build Back Better concept, which has increased its relevance in the international community after the Sendai Framework, can improve the quality of Indonesia's disaster resilience. Meanwhile, the research method applied is descriptive by looking at a case study of Japan's implementation of Build Back Better in Central Sulawesi after the 2018 Central Sulawesi Earthquake and Tsunami. The results obtained are that there are three Build Back Better projects carried out by Japan which contribute to Indonesia's disaster resilience through 1) improving the quality of infrastructure, management systems, and disaster technology in Central Sulawesi, 2) creating disaster-aware communities and revitalizing local communities in Central Sulawesi, and 3) becoming a model for Indonesia's independent implementation of Build Back Better and as proof of concept for ideas contained in Indonesia's national-level plans such as the 2015-2019 National Disaster Management Plan (RENAS PB 2015-2019).